THE INFLUENCE OF CLASS MANAGEMENT AND LEARNING BEHAVIOR TOWARD UNDERSTANDING LEVEL OF STUDENTS ClASS XI ANNIZAM MEDAN - Rifa’i, Muhammad; Mawaddah, Rahmiyatul (Universitas Nurul Jadid, 2020)
This study aims to analyse the phenomena of classroom management and student learning behavior while in learning and to the level of understanding of accounting cycle XI AK SMK An-Nizam Medan. This research use associative method, and sample of this research is counted 100 student class XI academic. Data collection techniques used are: Indirect communication techniques and direct communication. The data collection tool are; Questionnaire research, Interview. The results showed that; (1) There is partial influence of class management on the level of students' understanding. (2) There is partial influence of learning behavior toward level of understanding of student of class XI AK SMK An-Nizam Medan with value of sig 0,036 <0,050. (3) There is a linear influence between classroom management on learning behavior with deviation from linierity 0,073> 0,050 siginifikansi value. (4) There is significant and positive influence simultaneously class management and learning behavior toward student understanding level shown significance value 0,002 <0,050, and big influence of determination coefficient (R²) equal to 35%.